Regulatory Sandboxes: Global Experiences and Lessons for Ho Chi Minh City in Implementing the National Assembly’s Resolution No. 98/2023/QH15 - Nguyen , Xuan Truong (Journal of Finance - Marketing Research, 2025)
The rapid expansion of digital technologies has intensified regulatory challenges related to innovation, market stability, and consumer protection. Regulatory sandboxes, controlled environments for supervised experimentation, have emerged as key adaptive regulatory tools. This study conducts a PRISMA-based systematic review of 94 eligible studies drawn from academic databases and international institutional sources to examine global sandbox governance, operational models, performance indicators, and implementation challenges. Findings show that sandboxes function as policy learning laboratories, enabling regulators to test emerging technologies, reduce information asymmetries, and refine legal frameworks. Cross-country comparisons reveal substantial variation in governance design, inclusiveness, and market impact. Common challenges include resource constraints, inconsistent participation rates, limited data availability, and cross-border regulatory fragmentation. Effective practices identified across jurisdictions include digitally enabled supervision, standardized KPIs, hybrid sandbox–innovation hub models, and international coordination mechanisms. The study offers evidence-based recommendations to support Vietnam, particularly Ho Chi Minh City, in implementing experimental and adaptive regulatory mechanisms aligned with Resolution 98/2023/QH15.